2018
DOI: 10.1371/journal.pone.0190676
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and abnormal glucose tolerance in offspring of diabetic mothers: A systematic review and meta-analysis

Abstract: BackgroundRising prevalence of childhood obesity and type 2 diabetes mellitus (T2DM) is an emerging public health issue.ObjectivesTo investigate the association of maternal hyperglycemia exposure during pregnancy with obesity and abnormal glucose tolerance in offspring, and the age at occurrence.MethodsWe searched MEDLINE and EMBASE for observational studies on obesity and diabetes in offspring of diabetic mothers (gestational diabetes mellitus (GDM), type 1 diabetes mellitus (T1DM) and T2DM), and those on non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 36 publications
(141 reference statements)
5
99
1
7
Order By: Relevance
“…Similar results have been reported in a cohort of 618 mother and child dyads; the authors found associations between maternal hypertension and offspring risk of overweight or obesity at 4 years of age. Similarly, there are previous reports of an association between maternal GDM and offspring adiposity, although a recent systematic review concluded that the relationship between GDM and offspring BMI z‐score was not evident following adjustment for maternal BMI …”
Section: Discussionmentioning
confidence: 64%
“…Similar results have been reported in a cohort of 618 mother and child dyads; the authors found associations between maternal hypertension and offspring risk of overweight or obesity at 4 years of age. Similarly, there are previous reports of an association between maternal GDM and offspring adiposity, although a recent systematic review concluded that the relationship between GDM and offspring BMI z‐score was not evident following adjustment for maternal BMI …”
Section: Discussionmentioning
confidence: 64%
“…Independent of genetic risk, offspring born from diabetic pregnancies experience a greater risk of insulin resistance, pancreatic islet dysfunction and type 2 diabetes (Ratner et al 2008, Fraser & Lawlor 2014, Tam et al 2017, Das Gupta et al 2018. Such risk of transmission is thought to result from maternal hyperglycemia (Kubo et al 2014, Tam et al 2017, Kawasaki et al 2018; however, no direct evidence exists elucidating the exact role of maternal hyperglycemia in programming offspring metabolic health. Our fetomaternal hyperglycemia model, capable of inducing localized maternal and fetal hyperglycemia, addresses this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…Полученные нами данные также можно объяснить общностью генетических механизмов СД-2 и ГСД. Сегодня доказано, что развитие СД является следствием генетической предрасположенности к заболеванию [40][41][42][43][44][45][46][47][48][49][50]. К развитию ГСД и СД-2 причастны полиморфизмы тождественных генов [41][42][43], отвечающих за синтез и секрецию инсулина (INS, KCNJ11, АВСС8, TCF7L2, ND1), связанных с передачей инсулинового сигнала (INSR, IGF2, IRS1), регулирующих углеводный и липидный обмены (PPARG, PPARGC1A, ADRB3, GLUT1, ADIPOQ, FOXC2) и пр.…”
Section: таблицаunclassified